Evaluation of YouTube Videos as a Source of Patient Information for Ureteric Stent Placement: A Quality Assessment Study - Chaudhary, Kapil; Chandna, Abhishek; Kumar Devana, Sudheer; Sharma, Aditya Prakash; Tyagi, Shantanu; Singh, Shrawan K. (Frontiers in Surgery, 2022)
Abstract Objective To assess the quality of YouTube videos on ureteric stent placement (USP) as a source of patient available Methods YouTube was searched using search terms “DJ stenting”, “Double J stenting” and “ureteric stenting”. The initial 100 videos displayed with each of the above mentioned search terms were scrutinized. The selected videos reviewed by 3 independent consultant urologists against a pre-agreed scoring system based upon European association of Urology (EAU) patient information sheet on ureteric stent placement. The videos were scored qualitatively and quantitatively based on the scores achieved in various domains of the scoring Performa. Data was also collected for the number of views, likes, dislikes and time duration of each video. Results A total of 22 videos which fulfilled the inclusion criteria were reviewed. All the videos were uploaded by healthcare organizations or healthcare websites. None of the videos were classified as ‘Good’ based on reviewer scores and only one video was classified as ‘acceptable’. Fourteen videos were classified as ‘very poor’ with a score of less than 5/20. General information about stents was described by majority of the studies whilst preoperative information, procedure description, danger signs and follow up were scarcely described by most videos. Conclusion Majority of YouTube videos on USP are of poor overall quality and lack pertinent information. This calls for creation of comprehensive and unbiased videos for patient information on USP.